1980
DOI: 10.1073/pnas.77.2.698
|View full text |Cite
|
Sign up to set email alerts
|

Hydroboration kinetics: Unusual kinetics for the reaction of 9-borabicyclo[3.3.1]nonane with representative alkenes

Abstract: The kinetics of hydroboration of alkenes with 9-borabicyclo[3.3.lnonane dimer, (9-BBN)2, exhibit interesting characteristics. With more reactive alkenes, such as 1-hexene, 2-methyl-1-pentene, 3,3-dimethyl-1-butene, and cyclopentene, the reaction exhibits first-order kinetics, first order in (9-BBN)2 and zero order in alkene. On the other hand, with less reactive alkenes, such as cyclohexene, 1-methylcyclohexene, and 2,3-dimethyl-2-butene, the reaction exhibits three-halves-order kinetics, first order in alkene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…The observation of a reaction order of 0.4 for the BI autocatalyst indicates that some of it is tied up in an inactive form that has to dissociate first to liberate the free BI, similar to the case observed in some hydroborations involving borane dimers [35] . In fact, our NMR monitoring of the stoichiometric reaction of SIPr ( 1 a ) with anisaldehyde (2 b ) revealed that the Breslow intermediate BI 1a,2b forms an H‐bonded aggregate BI 1a,2b ⋅ 1 a (see Scheme 5, bottom left) with SIPr ( 1 a ).…”
Section: Resultssupporting
confidence: 64%
“…The observation of a reaction order of 0.4 for the BI autocatalyst indicates that some of it is tied up in an inactive form that has to dissociate first to liberate the free BI, similar to the case observed in some hydroborations involving borane dimers [35] . In fact, our NMR monitoring of the stoichiometric reaction of SIPr ( 1 a ) with anisaldehyde (2 b ) revealed that the Breslow intermediate BI 1a,2b forms an H‐bonded aggregate BI 1a,2b ⋅ 1 a (see Scheme 5, bottom left) with SIPr ( 1 a ).…”
Section: Resultssupporting
confidence: 64%
“…In situ 19 F-NMR spectroscopic analysis of the reaction of alkyne 2 with 1pin catalyzed by (9-BBN)2, revealed a similar but not identical set of intermediates to those found for Cy2BH. In situ 11 B NMR spectroscopic analysis also confirmed that the free 9-BBN is predominantly dimeric (K0 <1.4´10 -4 M; k0 ~1 ´10 -3 s -1 ) 40 under the reaction conditions. Independent reaction of alkyne 2 with 9-BBN generated E-49BBN and the double hydroboration 28 product 5(9BBN)2, which was also detected (0.8%) during catalytic turnover.…”
Section: Catalysis By 9-bbnmentioning
confidence: 71%
“…[5a] The reactions were monitored by 1 HNMR spectroscopyu ntil high conversionsw ere achieved. The relative rates of reaction for each substituted styrene were then calculated from the ratio of logarithmic fractional conversions, [23] also knowna st he Ingold-Shaw expression [24] (see Section3.2 in the Supporting Information). Linear free-energy relationships were constructed by plotting the decadic logarithms of the relative rates against various parameters of the styrene substituents.…”
Section: Resultsmentioning
confidence: 99%